2010
DOI: 10.1016/j.ijindorg.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, exports and productivity

Abstract: a b s t r a c t a r t i c l e i n f o We argue that the positive association found between firm productivity and exports in the literature relates to the firm's innovation decisions. Using a panel of Spanish manufacturing firms we find strong evidence that product innovation and not process innovation affects productivity and induces small non exporting firms to enter the export market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
185
2
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(219 citation statements)
references
References 24 publications
17
185
2
15
Order By: Relevance
“…The estimated coefficient of process innovation is also positive and significant in all estimations, which indicates that the use of a new or recent technology positively impacts the capacity of an entrepreneurial firm to internationalize. The magnitude of the marginal effect is 5.5%, which is lower than that for a new product and is consistent with other studies on incumbent firms that distinguish between product and process innovators that have found that product innovation has greater impact on internationalization than process innovation (Caldera, 2010;Cassiman et al, 2010). The positive coefficient of product and process innovations indicates that entrepreneurial firms that offer new products and use new technology are more export oriented than other young entrepreneurial firms; thus, proposing a new product and using a new technology increases the probability that an entrepreneur is internationalized by 9.4%.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The estimated coefficient of process innovation is also positive and significant in all estimations, which indicates that the use of a new or recent technology positively impacts the capacity of an entrepreneurial firm to internationalize. The magnitude of the marginal effect is 5.5%, which is lower than that for a new product and is consistent with other studies on incumbent firms that distinguish between product and process innovators that have found that product innovation has greater impact on internationalization than process innovation (Caldera, 2010;Cassiman et al, 2010). The positive coefficient of product and process innovations indicates that entrepreneurial firms that offer new products and use new technology are more export oriented than other young entrepreneurial firms; thus, proposing a new product and using a new technology increases the probability that an entrepreneur is internationalized by 9.4%.…”
Section: Resultssupporting
confidence: 89%
“…Third, product innovation may result in higher quality products, which increases the probability of internationalization (Roper and Love, 2002). Fourth, the impact of product innovation on internationalization is expected to be particularly strong for young entrepreneurial firms because product innovation dominates the early stage of the product life cycle (Cassiman et al, 2010).…”
Section: Innovation and Internationalizationmentioning
confidence: 99%
“…9 As a further check, we conduct a placebo test, that is, we randomly generate a year of the VAT pilot reform between 2000 and 2006 (as we need to include two years of lag and at least one post-reform period), and randomly select 38 out of 414 cities to be the reform sites (as the 2004 VAT pilot reform took place in 38 cities). 10 Based on these random draws, we then construct a false VAT pilot reform variable ( ] V AT c;t ), and use ] V AT c;t as the regressor of interest in a reduced-form regression similar to equation (5), 11 i.e., EXP f;i;c;t = ] V AT c;t + X 0 f;i;c;t 1 + i + c + t + " f;i;c;t :…”
Section: Resultsmentioning
confidence: 99%
“…10 We thank an anonymous referee for this suggestion. 11 It is not proper to perform an instrumental variable estimation using equation (5), as ] V AT c;t does not have explanatory power in the …rst stage.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, widespread evidence on the existence of important productivity differences between exporters and non-exporters in the period preceding foreign market entry (Wagner 2007) has stimulated a growing stream of literature aimed at analysing the sources of such disparity. Some papers, therefore, have rethought the relationship between a firm's innovation efforts and its export performance and have tested the hypothesis that product innovation has both a direct and mediate -through productivity -effect on exporting (Cassiman, Golovko, and Martínez-Ros 2010;Cassiman and Golovko 2011). Caldera (2010) reverses this view and, building on Bustos (2011), models more productive firms as self-selecting into innovation and innovators as being more likely to become exporters, due to the marginal cost reduction effect of innovation.…”
Section: Introductionmentioning
confidence: 99%